Brazilian neutrospheric delay (ZTD) temporal series and development of a climatology over nine-years data from soundering and GNSS - Albuquerque, Afonso Marques [UNESP]; Gouveia, Tayná Aparecida Ferreira [UNESP]; Alves, Daniele Barroca Marra [UNESP]; Jerez, Gabriel Oliveira [UNESP] (Springer Nature, 2025)
The Zenith Total Delay (ZTD) is one of the main sources of error associated with the neutrosphere in Global Navigation Satellite System (GNSS). This error can be estimated through GNSS processing and determined via in situ measurements, such as those obtained from radiosondes and other techniques. The zenith delay, caused by the neutrosphere, is influenced by local atmospheric conditions. In Brazil, owing to its proximity to the equator and the presence of the Amazon rainforest, the atmospheric behavior is distinctive and highly variable. This makes the country particularly affected by this effect, which is an important focus of related studies. In this study, ZTD maps were generated for the Brazilian territory via data from 31 radiosonde stations and 31 GNSS stations, covering a period of nine years (2014–2022). The observations used were at 0 and 12 UTC (Coordinated Universal Time). The analysis involved comparing ZTD values obtained from radiosondes and the GNSS and evaluating the data quality via both methods. Kriging techniques were employed to generate delay maps, both for a general scenario and for different seasons. The quality of the maps was validated via the cross-validation technique, which achieved an approximately 98% coefficient of determination and a root-mean-square error of 1.62 cm.